Optimizing Legal Education for Effective Crowd Control: A Case Study at SPN Polda Sulsel - Wahid, Abdhika Salafi; Tahir, Heri; Dahri, Irsyad; Pabali, Adeni Muhan Daeng; Najamuddin (Jurnal Ilmu Kepolisian, 2025)
This study aims to examine the variables influencing the South Sulawesi Regional Police Police Academy's inadequate crowd control law resources. The curriculum was ostensibly developed to provide adequate legal education, such as human rights, the proportionality of force, and pertinent standard operating procedures (SOPs); however, comprehensive interviews, direct observations, and document reviews reveal deep discrepancies between taught and practiced legal education. The study identifies that the limitations in the practical training component result from inadequately simulated practical sessions, short duration of the training, and obsolete training apparatus, which do not allow the cadets to attain the necessary skills. These gaps were recently manifested in Makassar, where ill-advised forceful actions against demonstrators were taken, signifying an operational standard far removed from the theoretical one. This was achieved through using qualitative legal methodology. These findings support strategic interventions intended to ensure that legal action officers are better prepared theoretically and practically to manage crowd control in a manner that respects human rights and fosters public confidence.